2020
DOI: 10.1021/acs.oprd.0c00185
|View full text |Cite
|
Sign up to set email alerts
|

Development and Execution of a Production-Scale Continuous [2 + 2] Photocycloaddition

Abstract: This article details the approach to large-scale production of cyclobutane 2 by the continuous-flow [2 + 2] photocycloaddition of maleic anhydride and ethylene, including (1) focused reaction optimization and development of a robust isolation protocol, (2) the approach to equipment design and process safety, and (3) the results of commissioning tests and production runs delivering the target compound at throughputs exceeding 5 kg/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…With the scalability of the synthesis of cyclobutanes from ethylene being demonstrated by the Kappe group on the hundred-gram scale [70], no attempts had been reported of performing this reaction on manufacturing scale. Recently, Beaver, Zhang and co-workers set out to develop a continuous flow platform for the synthesis of cyclobutane 34 (Scheme 11) in order to prepare >5 kg/day of the target compound [72]. To achieve this, a multistage approach was executed.…”
Section: Production Scale (> 1 Kg/day)mentioning
confidence: 99%
See 3 more Smart Citations
“…With the scalability of the synthesis of cyclobutanes from ethylene being demonstrated by the Kappe group on the hundred-gram scale [70], no attempts had been reported of performing this reaction on manufacturing scale. Recently, Beaver, Zhang and co-workers set out to develop a continuous flow platform for the synthesis of cyclobutane 34 (Scheme 11) in order to prepare >5 kg/day of the target compound [72]. To achieve this, a multistage approach was executed.…”
Section: Production Scale (> 1 Kg/day)mentioning
confidence: 99%
“…Comparison of this methodology to the previously published FEP reactor [9] found the Firefly system to be almost 30% more power efficient which while not crucial on laboratory scale, is of prime importance for manufacturing. The majority of novel innovative reactor designs for kilogram-scale continuous flow photochemical synthesis have only been reported over the last decade [20,61,72,[75][76][77]. Many of these involve scaling up reactors that were designed for laboratory scale synthesis, such as the vortex reactor reported by Poliakoff, George and coworkers [22,76].…”
Section: Production Scale (> 1 Kg/day)mentioning
confidence: 99%
See 2 more Smart Citations
“…While the reaction had been optimized using laser-based reactor configurations, laser equipment was not available to Asymchem within the desired timeframe (1-2 months) so efforts were directed towards scaling the reaction using LEDs as the light source in conjunction with a plug flow reactor (PFR). [34][35][36][37] Asymchem had previous success scaling similar reactors using UV LEDs 10,11 and several different research groups have reported success using such reactions on scales up to 1 kg but greater scales were not known at the time but have been reported since. 34,37 After an LED-PFR system was selected, the focus became identifying stable feed solutions for the initial scale-up.…”
Section: Manuscriptmentioning
confidence: 99%